Application of the educational process of progressive ideas of scientists teachers in previous years (Experimental biology, 2016)
This article describes the stages of pedagogical ideas of scientists teachers nineteenth and twentieth centuries, including pedagogical heritage of the famous American philosopher, educator John Dewey. Considered didactic principles, methods and instructional techniques in training and educating students. Shows the actual experience J. Dewey in modern educational practice, as well as pragmatic pedagogy scientists have been adopted in many countries around the world.Especially true his idea that the objectives of the new progressive school, he saw in the development of children for their reflective thinking and adaptation - active, independent people as individuals.
Keywords: conception; democracy; innovation; pedagogical technology; problem educating; method.